2023
DOI: 10.1093/pcmedi/pbad005
|View full text |Cite
|
Sign up to set email alerts
|

Circulating metabolic signatures of heart failure in precision cardiology

Abstract: Precision cardiology aims to implement personalized health care and precise medical decisions based on the specific characteristics of individuals. Metabolic remodeling plays a causal role in the pathogenesis of heart failure (HF). Changes in metabolic pathways such as substrate preference, high-energy phosphate metabolism and amino acid metabolism, are involved in pathological structural remodeling and functional impairment. These metabolic alterations are usually not restricted in the cardiac tissue, but als… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 150 publications
(145 reference statements)
0
9
1
Order By: Relevance
“…[62] However, glycolysis was significantly reduced and mitochondrial enzyme activity was impaired only in FCX. In contrast to the results of the previous study, Xie J et al found that glycolysis and lactylation were increased in the hippocampus of SCZ mice induced by MK-801 (0.4 mg kg −1 d −1 , 13d), and that an inhibitor of glycolysis (2-DG) ameliorated the behavioral abnormalities in SCZ mice [63] In addition, subcutaneous injection of MK-801 (0.2 mg kg −1 d −1 , 4d) in neonatal male Wistar rats transiently blocked the medial prefrontal cortex (mPFC) region of NMDA receptors that can lead to disturbances in energy metabolism and inhibited the rise in lactate levels caused by plantar stress, [64] which did not have a significant effect on adult rats. However, in another study, it was found that, given the same dose of MK-801, extracellular lactate concentration (eLAC) in the mPFC of adult male Wistar rats was elevated above the baseline level (≈65 μ L −1 ) and that MK-801 prolonged the transient elevation of eLAC induced by foot stress.…”
Section: Animal Models Of Schizophrenia and Abnormal Lactate Metabolismcontrasting
confidence: 83%
See 1 more Smart Citation
“…[62] However, glycolysis was significantly reduced and mitochondrial enzyme activity was impaired only in FCX. In contrast to the results of the previous study, Xie J et al found that glycolysis and lactylation were increased in the hippocampus of SCZ mice induced by MK-801 (0.4 mg kg −1 d −1 , 13d), and that an inhibitor of glycolysis (2-DG) ameliorated the behavioral abnormalities in SCZ mice [63] In addition, subcutaneous injection of MK-801 (0.2 mg kg −1 d −1 , 4d) in neonatal male Wistar rats transiently blocked the medial prefrontal cortex (mPFC) region of NMDA receptors that can lead to disturbances in energy metabolism and inhibited the rise in lactate levels caused by plantar stress, [64] which did not have a significant effect on adult rats. However, in another study, it was found that, given the same dose of MK-801, extracellular lactate concentration (eLAC) in the mPFC of adult male Wistar rats was elevated above the baseline level (≈65 μ L −1 ) and that MK-801 prolonged the transient elevation of eLAC induced by foot stress.…”
Section: Animal Models Of Schizophrenia and Abnormal Lactate Metabolismcontrasting
confidence: 83%
“…Abnormalities in lactate metabolism are prevalent in the brain [43,[55][56][57][58][59] and blood [19,21,60,61] of patients with schizophrenia, as well as in the brains of animal models of SCZ. [43,[62][63][64][65][66][67][68][69][70][71] Currently, in addition to the determination of blood lactate levels in schizophrenic patients by GC × GC-TOFMS-based small-polarity metabolite analysis platforms, [60] CE-TOFMS and LC-TOFMS, [61] fully automated blood gas analyzers, [21] stoichiometrically related nuclear magnetic resonance (NMR) analyses, [19] and highperformance liquid chromatography (HPLC), [72] magnetic resonance spectroscopy (MRS) [56,58,59] and 7-Tesla MRI [57] have been increasingly used for the detection of brain lactate levels in patients with SCZ. Most studies of animal models of SCZ have examined their brain lactate, with commonly used assays including 13C and 1H MRS, [62,66] 11.7 T MRS, [67] microdialysis, [65] R fu, [70] and lactate kits.…”
Section: Schizophrenia and Lactate Metabolism Disturbancementioning
confidence: 99%
“…[79,80] Increased FA dependency in diabetic cardiomyopathy Disturbances in lipid metabolism are detected during the early stages of diabetes and cardiac diseases. [81,82] Circulating levels of FAs increase in both T1DM and T2DM [83,84] because of impaired insulin action in the lipolysis of adipose tissues and the liver. [85,86] In addition, the increase in circulating FAs suppresses glucose uptake and oxidation.…”
Section: Multiple Fates Of Glucose In Diabetic Cardiomyopathymentioning
confidence: 99%
“…The heart contracts incessantly to supply oxygenated blood to the entire body and thus, requires a constant source of energy to fuel its high energy demands . The heart is a “metabolic omnivore” that utilizes a variety of fuel substrates, ranging from very polar (e.g., amino acid and nucleosides) to very nonpolar (e.g., lipids). Therefore, a comprehensive metabolomic analysis is critical to understanding cardiac metabolism; however, it remains challenging as the broad range of metabolite polarities makes extraction and detection difficult. …”
Section: Introductionmentioning
confidence: 99%